2020
DOI: 10.5267/j.msl.2019.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management processes and innovation performance: The moderating effect of employees’ knowledge hoarding

Abstract: The positive impact of knowledge management on innovation performance is no longer a mystery. However, the moderating role of knowledge hoarding remains undisclosed. Therefore, the present study aims to explore the moderating role of knowledge hoarding on the effect of knowledge management on innovation performance. On the ground of its design as a descriptive research, a questionnaire-based survey was developed, validated, and administered to a sample of 314 managers chosen from commerce and service organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…This allows determining the existence of a high correlation between the variables Application and use of Knowledge and continuous improvement in a Private University from Lima, 2020. These results are consistent with what Al-Abbadia, et al (2020), who carried out a study in service and commerce companies, where they affirm that the application of knowledge exerts a positive effect on the performance of innovation, since a p <0.05 was obtained. Ngoc-Tan and Gregar (2018) demonstrated that the use of knowledge is significantly associated with administrative innovation and technical innovation in the scenarios of public universities in Vietnam, obtaining a p value (sig = 0.006) lower than the significance level of 5%.…”
Section: Specific Hypothesis Test 3 Hosupporting
confidence: 92%
See 1 more Smart Citation
“…This allows determining the existence of a high correlation between the variables Application and use of Knowledge and continuous improvement in a Private University from Lima, 2020. These results are consistent with what Al-Abbadia, et al (2020), who carried out a study in service and commerce companies, where they affirm that the application of knowledge exerts a positive effect on the performance of innovation, since a p <0.05 was obtained. Ngoc-Tan and Gregar (2018) demonstrated that the use of knowledge is significantly associated with administrative innovation and technical innovation in the scenarios of public universities in Vietnam, obtaining a p value (sig = 0.006) lower than the significance level of 5%.…”
Section: Specific Hypothesis Test 3 Hosupporting
confidence: 92%
“…The result is supported by what the Garcia-Fernandez (2016) research mentions, who refers to the knowledge storage variable, determining that companies with higher levels of knowledge storage tend to use tools such as the intranet or databases , being the head of the area responsible for storing the knowledge; This allows the company to obtain the knowledge generated quickly, which facilitates making modifications to its products or processes in order to adapt them to the needs of the company in the face of changes in the market. Likewise, Al-Abbadia et al (2020) state that the storage of knowledge in trade and service organizations exerts a positive effect on the performance of innovation, since a p <0.05 was obtained. This study recommends that companies should focus on the nature of knowledge that employees possess, in order to verify their role and use it to contribute to business innovation.…”
Section: Specific Hypothesis Test 2 Homentioning
confidence: 96%
“…The concept of KHo is presented in only 13 articles (Al‐Abbadia et al, 2020; Anaza & Nowlin, 2017; Connelly et al, 2012; Evans et al, 2015; Feng & Wang, 2019; Garg & Anand, 2020; Holten, Hancock, Persson, Hansen, & Hogh, 2016; Pan, Zhang, Teo, & Lim, 2018; Serenko & Bontis, 2016; Su, 2020; Wang, Han, Xiang, & Hampson, 2019b; Wang, Law, Zhang, Li, & Liang, 2019a; Xia et al, 2019; Zhao et al, 2016). In those articles, KHo is defined as knowledge retention, in 5 of them (Anaza & Nowlin, 2017; Feng & Wang, 2019; Holten et al, 2016; Pan et al, 2018; Zhao et al, 2016) it is also explicit that the retained knowledge is not requested.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Commitment is the degree to which an employee identifies with the organization and wants to continue actively participating in it, willing to put forth effort on its behalf [40] [26]. Commitment also reflected as a force that binds an individual to a course of action of relevance to one or more targets, reliable identification of someone with their duties, and self-identification, loyalty, and involvement expressed by someone [41]- [43].…”
Section: Affective Commitment and Professional Performancementioning
confidence: 99%
“…Organizational commitment, among others, affective commitment, which involves the employees' emotional attachment to, identification with, and involvement in the organization [46]. For Newstrom [40], affective commitment is the employees' positive emotions to try and choose to remain part of the organization. Like the arguments, Ivancevich, Konopaske & Matteson [3] state that commitment involves many attitudes reflected affection, such as feelings are identical to organizational goals, a sense of being involved in organizational tasks, and feeling loyal to the organization.…”
Section: Affective Commitment and Professional Performancementioning
confidence: 99%